2016
DOI: 10.1074/jbc.m116.721597
|View full text |Cite
|
Sign up to set email alerts
|

Endo-F3 Glycosynthase Mutants Enable Chemoenzymatic Synthesis of Core-fucosylated Triantennary Complex Type Glycopeptides and Glycoproteins

Abstract: Chemoenzymatic synthesis is emerging as a promising approach to the synthesis of homogeneous glycopeptides and glycoproteins highly demanded for functional glycomics studies, but its generality relies on the availability of a range of enzymes with high catalytic efficiency and well defined substrate specificity. We describe in this paper the discovery of glycosynthase mutants derived from Elizabethkingia meningoseptica endoglycosidase F3 (Endo-F3) of the GH18 family, which are devoid of the inherent hydrolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
115
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 80 publications
(91 reference statements)
0
115
0
Order By: Relevance
“…We have recently reported that a high-level, soluble expression of Endo-F3 and its mutants could be achieved using this vector (32). Following a similar method, the Endo-S2 was successfully expressed in Escherichia coli and was readily purified using immobilized metal ion affinity chromatography to obtain the soluble enzyme with a yield of more than 20 mg/liters.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…We have recently reported that a high-level, soluble expression of Endo-F3 and its mutants could be achieved using this vector (32). Following a similar method, the Endo-S2 was successfully expressed in Escherichia coli and was readily purified using immobilized metal ion affinity chromatography to obtain the soluble enzyme with a yield of more than 20 mg/liters.…”
Section: Resultsmentioning
confidence: 98%
“…These include a key asparagine residue for endoglycosidases Endo-A (Asn-171) (36), Endo-M (Asn-175) (37,38), and Endo-D (Asn-322) (24) of the GH85 family, or a key aspartic acid residue for the GH18 family endoglycosidases Endo-S (Asp-233) (25) and Endo-F3 (Asp-165) (32). Sequence alignment of Endo-S2 and Endo-S revealed that the Asp-184 of Endo-S2 was the residue equivalent to Asp-233 of Endo-S essential for promoting oxazolinium ion formation in hydrolysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transglycosylation onto ␣1,6-fucosyl GlcNAc moieties by endoglycosidase was first reported in Endo-F2 and Endo-F3 (41). Recently, Endo-F3 was converted to a glycosynthase, and the mutant enzyme was capable of transferring bi-and triantennary complex type N-glycans using sugar oxazoline donor substrates to synthesize core-fucosylated complex glycopeptides (42). Endo-S and its glycosynthase, which specifically and efficiently acts on the IgG-Fc domain of N-glycans, have been used for chemoenzymatic synthesis of IgGs with structurally defined glycoforms for functional studies (43)(44)(45).…”
mentioning
confidence: 99%